Strong founder effect for a transglutaminase 1 gene mutation in lamellar ichthyosis and congenital ichthyosiform erythroderma from Norway - Pigg, Maritta; Gedde-Dahl, Tobias; Cox, Diane; Haußer-Siller, Ingrid; Anton-Lamprecht, Ingrun; Dahl, Niklas (European journal of human genetics, 1998)
Autosomal recessive congenital ichtyosis (ARCI) is a clinically heterogeneous disorder of keratinisation. It was recently shown that mutations in the transglutaminase 1 (TGM1) gene may be associated with the clinical subtypes lamellar ichthyosis (LI) and non-bullous congenital ichthyosiform erythroderma (CIE). Thirty-six Norwegian families with LI and seven with non-bullous CIE were studied with microsatellite markers linked to the TGMI gene. One common halpotype for two markers was found on 74% of disease associated chromosomes. Three individuals homozygous for the common haplotype, two affected by LI and one affected by CIE, were analysed for mutations in the TGM1 gene. All three patients were found homozygous for a single A to G transition located in the canonical splice acceptor site of intron 5. Probands from the remaining 40 families with LI and CIE were screened for this mutation and the A to G transition was found on 61 out of 72 alleles associated with LI and on 9 out of 15 alleles associated with CIE. These findings suggest a single founder mutation for the majority of patients with LI and CIE in Norway. The 2526A→G mutation results in the insertion of a guanosine at position 877 (876insG) in the mature cDNA and the frame shift creates a premature termination at codon 293. The mutation was previously observed in one family with a resulting cDNA that included the entire intron 5. These results suggest that the mutation can result in variant transcripts in different individuals.
Gesehen am 19.10.2023